Evidence-based resistance training recommendations - Fisher, J.; Steele, J.; Bruce-Low, S.; Smith, D. (Medicina Sportiva, 2011)
Resistance training produces an array of health benefits, as well as the potential to promote muscular adaptations of strength, size, power and endurance. The American College of Sports Medicine (ACSM) regularly publish a position stand making recommendations for optimal achievement of the desired training goals. However, the most recent position stand (as well as previous ones) has come under heavy criticism for misrepresentation of research, lack of evidence and author bias. Therefore this paper proposes a set of scientifically rigorous resistance training guidelines, reviewing and summarising the relevant research for the purpose of proposing more logical, evidence-based training advice. We recommend that appreciably the same muscular strength and endurance adaptations can be attained by performing a single set of ~8-12 repetitions to momentary muscular failure, at a repetition duration that maintains muscular tension throughout the entire range of motion, for most major muscle groups once or twice each week. All resistance types (e.g. free-weights, resistance machines, bodyweight, etc.) show potential for increases in strength, with no significant difference between them, although resistance machines appear to pose a lower risk of injury. There is a lack of evidence to suggest that balance from free weights or use of unstable surfaces shows any transference to sporting improvement, and explosive movements are also not recommended as they present a high injury risk and no greater benefit than slow, controlled weight training. Finally, we consider genetic factors in relation to body type and growth potential.